Job optimization system / Asimah Sulaiman - Sulaiman, Asimah (2014)
Job Optimization System is an application that gives suggestion to the user of the suitable jobs based on the examination result. Previously, fresh graduate is lack of knowledge about choosing the job even though they have good examination result. The objective of this system is to apply, develop, and test the functionality of job optimization system using Case-Based Reasoning (CBR) method. This system will conduct the Case-Based Reasoning (CBR) to generate the new cases for suitable users based on examination result. Therefore, fresh graduate can get suggestion jobs. It focuses on graduates who undertake the Bachelor of Computer Science (Hons) in Faculty of Computer Science and Mathematics (FSKM) UiTM Shah Alam. The user will enter the examination result and the grade obtained for each courses.